Kosovo Policy Note : Public Administration Reform - Nagaki, Shiho (World Bank, Washington, DC, 2021)
The weak performance of public institutions in Kosovo challenges efficient public service delivery and could impede faster growth. Effective public administration is a key factor for an economy that aims to generate jobs and improve citizens’ well-being. The recently adopted Law on Salaries, Law on Public Officials, and Law on Organization and Functioning of State Administration and Independent Agencies provide a basis to improve public sector management and enable the country to ensure more effective and efficient service delivery to citizens and businesses. However, the Constitutional Court’s recent decision to suspend the laws on salary and public officials indicates the complex task of ensuring equality in human resources and pay management. Equality and transparency in the legal framework for public administration are critical for public sector performance and productivity.